POTENTIAL OF SEAWEED (Eucheuma cottonii) EXTRACT AS A HEPATOPROTECTOR IN RABBIT (Oryctolagus cuniculus) INDUCED ORGANOPHOSPHATE PESTICIDES - Alza Hamdi Putra; kholik kholik; novarina sulsia ista'in ningtyas (Jurnal Biosains Pascasarjana, 2022)
The use of organophosphate pesticides in developing countries is already widespread and can contaminate animal feed or human food ingredients which has an impact on liver damage and other organs. The use of seaweed containing polyphenols as a hepatoprotector for organophosphate poisoning has not been widely used by the public. The purpose of this study was to determine the potential of seaweed extract as a hepatoprotector in organophosphate-induced rabbits as seen from serum glutamate oxaloacetate transaminase (SGOT) and serum glutamate pyruvate transaminase (SGPT) levels. This study used a complete randomized design with 20 male rabbits as experimental animals which were divided into 4 treatments with 5 repetitions, namely: P0 was the control group which was only given distilled water, P1 was the group given seaweed extract at a dose of 200 mg/Kg BW, P2 is the group given seaweed extract at a dose of 400 mg/KgBB and P3 is the positive control group which is not given seaweed extract and distilled water. On the 15th day the P1, P2, and P3 groups were given profenofos pesticide at a dose of 50 mg/kg BW. The results showed a very significant difference (p-value = 0.02, α = 0.05) in SGOT levels between the P0 control group (135.4 ± 67.00 U/L) and the P1 treatment group (41.8 ± 17.45 U/L), P2 (25.8 ± 8.75 U/L), and the positive control group P3 (70 ± 29.04). The results of the study also found that there was no significant difference in SGPT levels in the P0 control group and the P1, P2, and P3 control groups. Giving seaweed extract with different doses provides a hepatoprotector effect by reducing the release of SGOT into the blood.